Interrater Agreement for Consensus Definitions of Delayed Ischemic Events After Aneurysmal Subarachnoid Hemorrhage. Issue 3 (June 2016) - Zafar, Sahar F.; Westover, M. Brandon; Gaspard, Nicolas; Gilmore, Emily J.; Foreman, Brandon P.; O'Connor, Kathryn L.; Rosenthal, Eric S.
Abstract : Background: Thirty percent of patients with subarachnoid hemorrhage experience delayed cerebral ischemia or delayed ischemic neurologic decline (DIND). Variability in the definitions of delayed ischemia makes outcome studies difficult to compare. A recent consensus statement advocates standardized definitions for delayed ischemia in clinical trials of subarachnoid hemorrhage. We sought to evaluate the interrater agreement of these definitions. Methods: Based on consensus definitions, we assessed for: (1) delayed cerebral infarction, defined as radiographic cerebral infarction; (2) DIND type 1 (DIND1), defined as focal neurologic decline; and (3) DIND2, defined as a global decline in arousal. Five neurologists retrospectively reviewed electronic records of 58 patients with subarachnoid hemorrhage. Three reviewers had access to and reviewed neuroradiology imaging. We assessed interrater agreement using the Gwet kappa statistic. Results: Interrater agreement statistics were excellent (95.83%) for overall agreement on the presence or absence of any delayed ischemic event (DIND1, DIND2, or delayed cerebral infarction). Agreement was "moderate" for specifically identifying DIND1 (56.58%) and DIND2 (48.66%) events. We observed greater agreement for DIND1 when there was a significant focal motor decline of at least 1 point in the motor score. There was fair agreement (39.20%) for identifying delayed cerebral infarction; CT imaging was the predominant modality. Conclusions: Consensus definitions for delayed cerebral ischemia yielded near-perfect overall agreement and can thus be applied in future large-scale studies. However, a strict process of adjudication, explicit thresholds for determining focal neurologic decline, and MRI techniques that better discriminate edema from infarction seem critical for reproducibility of determination of specific outcome phenotypes, and will be important for successful clinical trials.